Applied Philosophy and the Representation of the Other in Islamic Heritage:A Study of Al-Biruni’s Methodology: Applied Philosophy and the Representation of the Other in Islamic Heritage (Elmergib Journal of Human Sciences, 2026)
This study aims to identify the methodological and epistemological foundations adopted by al-Biruni in his study of religions, and to examine whether his contributions to this field represent a genuine experiment in applied philosophy. It also seeks to explore the relevance of al-Biruni's methodological model to our current reality. The analytical method was employed to deconstruct al-Biruni's concepts in the study of religions, along with comparative methods to determine the limitations of his judgments. The historical method was also used to examine the prevailing epistemological framework of his era, in order to understand the relationship between his methodology and the intellectual landscape of his time. The researcher concluded that al-Biruni presented a coherent approach to representing the "other," enabling him to integrate this type of study into the realm of applied philosophy, and that his writings in this area constitute a valuable intellectual legacy.
Keywords: Applied philosophy; Representing the other; Studying religions; Islamic thought; Cognitive structure